Ethnomicology and utilization potential of petir fungi (Lignosus sp.) at KPH Sengayam, Kotabaru, South Kalimantan - Safinah Surya Hakim; Eko Priyanto (Jurnal GALAM, 2020)
Known locally as the the lightning mushroom or tiger milk mushroom, Lignosus sp. is well-known as mushroom. Lignosus sp. is categorized as nontimber forest product which has potential to be developed due to its advantages. Interview and literature review were carried out during this study to investigate the ecology, ethnomycology, and economic potential of Lignosus sp. Study result showed that currently the fungi Lignosus sp. in Kotabaru Regency can be found around the forest area that is administratively included in the Muara Urie and Buluh Kuning Villages. Local community has been used this fungi as traditional medicine, such as for cough medicine and postnatal care for mothers. In addition, local people harvest this fungi and sell it to middleman. However, the information of cultivation of this mushroom still limited particularly in South Kalimantan. Therefore, further studies need to be investigate.